Ontological and Epistemological Implications of Black Hole Evaporation in Modern Physical Philosophy - Reza Ariefka; Taufik Roni Sahroni; Ruben Cornelius Siagian; Arip Nurahman; Abu Yazid Raisal (Jurnal Filsafat "WISDOM", 2026)
The research is motivated by developments in modern physics which show that black holes, which in classical general relativity are considered the most stable and permanent entities in the universe, actually undergo evaporation through Hawking radiation. This phenomenon has profound philosophical implications regarding the nature of physical existence, the status of information, the structure of space-time, and the direction of cosmological time. This research aims to analyse the ontological and epistemological implications of black hole evaporation in the context of micro-macro relationships, relational ontology, and the concept of time as a phenomenon that emerges from fundamental physical processes. This study employs a qualitative research method based on literature review and conceptual analysis, integrating perspectives from theoretical physics, philosophy of physics, and modern cosmology. The findings indicate that black hole evaporation confirms that there are no physical entities that are absolute and permanent. Physical existence is more accurately understood as a relational phenomenon that depends on the interaction between the geometry of space-time, quantum fluctuations, and cosmic thermodynamic processes. In addition, the black hole information paradox can be understood as a limitation of human epistemological description, not as an ontological loss of physical reality. This research also confirms that the direction of time is an emergent consequence of the increase in the entropy of the universe. The novelty of this research lies in the integration of the phenomenon of black hole evaporation with a structural-relational ontological approach to explain physical reality as a dynamic and emergent process.